Histo- pathological Characterization of malignant cutaneous melanoma. Cienfuegos Province. 2009-2011 - Zuria Elisa Ayala Reina; Martha R. González Debén; Janet Villafuerte Reinante; Yarisdey Corrales Hernández; Galia Ivis Pérez Rumbaut; Daimy Nualla Bolufé (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2018)
Foundation: malignant melanoma is the cause of most deaths due to cutaneous cancer and its prognosis depends greatly on its staging at the moment of the diagnosis. Objective: to characterize histo-pathologically cutaneous malignant melanoma in the Cienfuegos Province. Methods: retrospective descriptive study which included all the patients with the diagnosis of cutaneous malignant melanoma in the Cienfuegos Province between January 2000 to 2011. Clark 's variables , Breslow' s index, mitotic index, age and sex were analyzed Results: the predominant histological subtype is the superficial extensive melanoma, patients of the male sex predominated in ages from 50 to 69. A significant association between Clark's level, mitotic index and Breslow's index was shown. Conclusion: Breslow's index constitutes one of the prognosis factors of greater importance at present for the correct staging of the patient with cutaneous malignant melanoma.